Effect of image registration on 3D absorbed dose calculations in 177Lu-DOTATOC peptide receptor radionuclide therapy. (January 2018) - Grassi, Elisa; Fioroni, Federica; Berenato, Salvatore; Patterson, Nick; Ferri, Valentina; Braglia, Luca; Filice, Angelina; Versari, Annibale; Iori, Mauro; Spezi, Emiliano
Highlights: Image registration algorithm on 3D dose calculation in a PRRT trial. Registration of 5 sequential SPECT/CT scans. 5 SPECT/CT sequential scans after a single administration of 177 Lu-DOTATOC. Images were subsequently registered using rigid and deformable algorithms. Image based 3D dosimetry affected by the registration algorithm. Abstract: Peptide receptor radionuclide therapy (PRRT) is an effective MRT (molecular radiotherapy) treatment, which consists of multiple administrations of a radiopharmaceutical labelled with 177 Lu or 90 Y. Through sequential functional imaging a patient specific 3D dosimetry can be derived. Multiple scans should be previously co-registered to allow accurate absorbed dose calculations. The purpose of this study is to evaluate the impact of image registration algorithms on 3D absorbed dose calculation. A cohort of patients was extracted from the database of a clinical trial in PRRT. They were administered with a single administration of 177 Lu-DOTATOC. All patients underwent 5 SPECT/CT sequential scans at 1 h, 4 h, 24 h, 40 h, 70 h post-injection that were subsequently registered using rigid and deformable algorithms. A similarity index was calculated to compare rigid and deformable registration algorithms. 3D absorbed dose calculation was carried out with the Raydose Monte Carlo code. The similarity analysis demonstrated the superiority of the deformable registrations (p < .001). Average absorbed dose to the kidneys calculated using rigid image registration was consistently lower than the average absorbed dose calculated using the deformable algorithm (90% of cases), with percentage differences in the range [−19; +4]%. Absorbed dose to lesions were also consistently lower (90% of cases) when calculated with rigid image registration with absorbed dose differences in the range [−67.2; 100.7]%. Deformable image registration had a significant role in calculating 3D absorbed dose to organs or lesions with volumes smaller than 100 mL. Image based 3D dosimetry for 177 Lu-DOTATOC PRRT is significantly affected by the type of algorithm used to register sequential SPECT/CT scans.